SINTESIS SENYAWA p-METOKSIBENZIL ASETAT DAN p-METOKSIBENZILTIOL ASETAT DARI MINYAK ADAS DENGAN METODE SONIKASI, GELOMBANG MIKRO DAN PENGGERUSAN - , SYARIFUDDIN OKO,S.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The synthesis of p-methoxybenzyl acetate and p-methoxybenzylthiol acetate by using fennel oil as the starting material has been evaluated. The synthesis was carried out in five steps of reaction (1) oxidation of anethole by using KMnO4 under ultrasonic and microwave irradiation, (2) reduction pmethoxybenzaldehyde with NaBH4 in methanol using sonication and solventless grinding method, (3) esterification of p-methoxybenzyl alcohol and glacial acetic acid was conducted using sulfuric acid as catalyst, (4) p-methoxybenzyl thiol was synthesized from p-methoxybenzyl alcohol and thiourea in hyrochloric acid as catalyst, then hydrolyzed using NaOH, (5) esterification of p-methoxybenzyl thiol and acetic acid anhydride using TMEDA as catalyst carried out to p-methoxybenzylthiol acetate under ultrasonic irradiation. The structure elucidation was performed by FTIR spectrometer and GC-MS. Oxidation of anethole under ultrasonic and microwave irradiation produced a viscous yellow liquid of p-methoxybenzylaldehyde in 78.30% and 91.06 yield respectively. Reduction of p-methoxybenzaldehyde yielded 82.99 % and 92.00 % of a colorless viscous liquid of p-methoxybenzyl alcohol under sonication and grinding method, respectively. Esterification of p-methoxybenzyl alcohol and glacial acetic acid catalyzed by sulfuric acid produced p-methoxybenzyl acetate gave 40.19% in yield. The reaction of p-methoxybenzyl alcohol and thiourea in hydrochloric acid, then hydrolyzed in basic condition (NaOH) produced p-methoxybenzyl thiol in 80.89% yield. The product of p-methoxybenzylthiol acetate obtained by reaction of p-methoxybenzyl thiol with acetic acid anhydride and TMEDA as catalyst produced 0.76% in yield.